Antibacterial Potential Test of Henna Leaf Extract (Lawsonia inermis L.) Against Edwardsiella ictaluri - Nuklir, Silvia; Wahyuni, Fitra; Maritsa, Hasna Ul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
One of the bacterial pathogens that is often a serious concern in freshwater fish farming is Edwardsiella ictaluri, a causative agent of Enteric septicemia of catfish (ESC). Edwardsiella ictaluri which generally attacks catfish groups such as lele, patin, and sidat, but can also attack other species, such as tilapia. Therefore, alternative efforts are needed that are more environmentally friendly, safe for consumers, and do not trigger bacterial resistance. One of the plants that has the potential as a source of natural antibacterials is henna leaves (Lawsonia inermis L.). The purpose of this study was to determine the potential of henna leaf extract (Lawsonia inermis L.) as an antibacterial against Edwardsiella ictaluri and to determine the concentration of henna leaf extract (Lawsonia inermis L.) that is most effective in inhibiting the growth of Edwardsiella ictaluri bacteria. The method used in this study was disc diffusion. Analysis was conducted by testing the data for normality, homogeneity, kruskall wallis test and continued with the Dunn test using SPSS software version 26. The concentration of henna leaf extract of 3%, 6%, 12%, 24% and 48% is known to be able to inhibit the growth of Edwardsiella ictaluri bacteria with an average inhibition zone of 10.45 mm, 11.73 mm, 13.25 mm, 14.51 mm and 16.85 mm respectively. Henna leaf extract has the ability to inhibit the growth of Edwardsiella ictaluri bacteria with a strong category. A concentration of 48% is an effective concentration in inhibiting the growth of Edwardsiella ictaluri.